2021
DOI: 10.1590/0001-3765202120200991
|View full text |Cite
|
Sign up to set email alerts
|

Body size, age and growth in males populations of Boana pulchella (Anura, Hylidae)

Abstract: Age determination in amphibians is crucial to the investigation of life-history traits. In this context, we studied, for the fi rst time, the life-history traits of Boana pulchella from a sample (63 adult males) of three populations (Las Acequias, Río Cuarto, Alejandro Roca) in central Argentina using the skeletochronological method. All adults of B. pulchella studied showed recognizable bone structures that allowed age determination.The average snout-vent length of sexually mature males was 43.39 mm. The maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…The post-metamorphic terrestrial growth is a major part of total growth (over 90%) in amphibians (Werner, 1986) and the variation in terrestrial growth rates and age at maturity is playing an important role in the intersexual adult size variability (Marangoni et al, 2012). Furthermore, the age determination of amphibians yields crucial information on the demographic features such as size at sexual maturity growth, longevity, and growth rate (Duellman and Trueb, 1994;Otero et al, 2017;Baraquet et al, 2021). In this study, we found that the age is ranged between 2-6 years.…”
Section: Discussionmentioning
confidence: 46%
“…The post-metamorphic terrestrial growth is a major part of total growth (over 90%) in amphibians (Werner, 1986) and the variation in terrestrial growth rates and age at maturity is playing an important role in the intersexual adult size variability (Marangoni et al, 2012). Furthermore, the age determination of amphibians yields crucial information on the demographic features such as size at sexual maturity growth, longevity, and growth rate (Duellman and Trueb, 1994;Otero et al, 2017;Baraquet et al, 2021). In this study, we found that the age is ranged between 2-6 years.…”
Section: Discussionmentioning
confidence: 46%